THE IMPACT OF ENTREPRENEURSHIP EDUCATION TO ENTREPRENEUR INTENTION THROUGH PLANNED BEHAVIOUR AS INTERVENING VARIABLE (Study in Brawijaya University Students Have Partcipation the Entrepreneurship Education for 2016 study programs) - Baihaqi, Aufa Izzuddin; Arifin, Zainul; Mawardi, M. Kholid (The International Journal of Accounting and Business Society, 2019)
Although many researchers have focused on entrepreneurship education, little research has been done into the effects for students and the overall effectiveness of the university for entrepreneurship education programs in Indonesia. The research focused using theory of planned behavior and investigates the impact of entrepreneurship programs on the entrepreneur intention students in Brawijaya University. Data for this study is drawn from 9 faculty in Brawijaya University. Sample used in this research have 382 student 2016 period. The results show that participants of entrepreneurship education programs in brawijaya university have a positive effect on atitude toward entrepreneurship, subjective norm and perceived behavioral control. Variable atitude toward entrepreneurship, subjective norm and perceived behavioral control have a positive effect to entrepreneurial intention. Furthermore, the findings of this report entrepreneurship education to entrepreneur intention have a positive effect and significant through planned behaviour as intevening variable in Brawijaya University student 2016 period